Position and Role of Promotion in the Marketing Communication System at Company Level - PitinovaТ. В.; KhyzhnyakК. В. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
New types of advertizing have appeared apart from classical mass media due to the shrinking effectiveness of traditional advertizing messages. Promotions are not a brand new instrument for communicating and promoting goods and services to the market, but once organized and in a correct manner, they will be capable to bring success and good financial returns. Each promotion needs to be thoroughly elaborated and permanently controlled, being an instrument of marketing communications capable to have either positive or negative implications for the consumer attitude to a company. The objective of the study is to demonstrate the importance of promotions for company performance and effective communication with customers; to define the criteria for planning and organization of an effective promotion as part of marketing communication at company level. The essential meaning of promotion and its role in the system of marketing communications is highlighted. The most common mistakes in organizing promotions are shown; the criteria for effective planning of promotion campaign and the criteria for successful organization of a promotion are given.